Essay for a history of the Philosophy of Liberation in Brazil - Pansarelli, Daniel (2024)
This essay outlines an interpretive hypothesis aimed at providing elements for the future construction of the history of Philosophy of Liberation in Brazil. It begins with notes on the history of Brazilian philosophy, considering it primarily in two moments: first, during the lengthy colonial period, marked by Jesuit colleges and their Ratio Studiorum; then, in the contemporary university context, from the 20th century onwards, which still remains relevant. It discusses philosophical movements that, within the context of the Brazilian civic-military dictatorship, explicitly dedicated themselves to hindering the spread of Philosophy of Liberation in our country, and finally, it presents some of the main paths taken by this philosophical strand, from its earliest theses to its current configurations. In constructing the essay, specific productions on the theme within the context of graduate programs in Philosophy in Brazil are addressed, thus seeking to better elucidate the breadth of the proper philosophical presence of this line of thought in our midst.